THE EMOTIONAL DYNAMICS OF TEENAGERS IN HIGH SCHOOL STUDENTS FROM BROKEN HOMES - Lubis, Suaidah; Parinduri, Rusdah; Putri, Annisa; Rambe, Rifatun Nihayah; Ningrum, Sekar Dwi; Sari, Yuli Novia (LPPM Univ. Ibn Khaldun Bogor, 2025)
Some students at a state high school in Perbaungan exhibit disruptive behavior, harming themselves and disturbing the school environment. These students often skip school, ignore assignments, fight with classmates, disobey teachers, and cause disruptions. The root cause appears to be the students' backgrounds, particularly coming from broken homes. A broken home, caused by parental divorce, leads to emotional struggles in adolescents. This research aims to explore the emotional dynamics of adolescents from broken homes due to their parents' divorce. A qualitative approach with a case study method was used, involving three respondents aged 16 and 17 from divorced families, selected through purposive sampling. Triangulation techniques—source, method, and time—were applied for data validity. Descriptive analysis was employed to analyze the data collected from the informants. The findings show that all three respondents exhibited negative behavioral changes, emotional instability, and psychological trauma. They also reported a lack of attention and affection from their parents after the divorce. Despite the challenges, they viewed parental divorce as a process of self-maturation, although it was also seen as a difficult and painful experience.